Inteference Mitigation in Femtocellular Networks - Amevi Acakpovi; Dominique Kogue; Koudjo Mawuefam Koumadi; Ibrahim Tahirou (Institute of Advanced Engineering and Science, 2014)
Femtocells can significantly boost up wireless cellular network capacity by reducing communication distances to user equipment and also by reusing resources already utilized in the macrocell network on which they overlay. However, the deployment of femtocells within a macrocell coverage area, causes severe interference between the femtocell and the macrocell, which may have an impact on the overall performance of the femtocells. Avoiding such interference is very important for the effective co-existence of femtocells and macrocell. This paper proposes an algorithm to mitigate cross-tier interference between a femtocell and a macrocell using adaptive power control. The proposed approach is modeled and simulated using MATLAB. The impact on the performance of the femtocell using the proposed algorithm is analysed. Results show that the proposed adaptive power control algorithm has tremendously reduced the negative effects on the system throughput, delay and outage probability for voice and data traffics.